Cover Image, Volume 170A, Number 4, April 2016. Issue 4 (April 2016) - Scheps, Karen G.; Francipane, Liliana; Nevado, Julián; Basack, Nora; Attie, Myriam; Bergonzi, María Fernanda; Cerrone, Gloria E.; Lapunzina, Pablo; Varela, Viviana
Abstract : The cover image, by Karen G. Scheps et al., is based on the Research Article Multiple copy number variants in a pediatric patient with Hb H disease and intellectual disability, DOI:10.1002/ajmg.a.37532 .